PERANGKAP TIKUS MENGGUNAKAN MIKROKONTROLER DENGAN FASILITAS SHORT MESSAGE SERVICE (SMS) - Syamsudin, Eko; Wijono, F.X. Sigit; Gunawan, Hendra (Universitas Tarumanagara, 2008)
This paper will be discussing about the design of mouse trap based in microcontroller using SMS as a media. The purpose of this designing is to detect a mouse when it has been trapped by using infrared sensor, to inform mouse trapped by using short message service and also to instruct the microcontroller to activate the shocking element by sending back the SMS with a special command to this designing. This shocking element is installed inside the trap and be used for killing mouse with AC voltage 220 volt